2017
DOI: 10.1017/s1751731116001816
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ruminal fermentation characteristics and utilisable CP supply of sainfoin and birdsfoot trefoil silages and their mixtures with other legumes

Abstract: The extensive protein degradation occurring during ensiling decreases the nutritive value of silages, but this might be counteracted by tannins. Therefore, silages from two legume species containing condensed tannins (CT) – sainfoin (SF) and birdsfoot trefoil (two cultivars: birdsfoot trefoil, cv. Bull (BTB) and birdsfoot trefoil, cv. Polom) – were compared for their in vitro ruminal fermentation characteristics. The effect of combining them with two CT-free legume silages (lucerne (LU) and red clover (RC)) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 29 publications
12
28
1
Order By: Relevance
“…No mineral fertilizer was applied. To obtain three independent replicates (batches) per legume, fields were subdivided in three plots and sampling between two plots was performed at a distance of approximately 150 m (Grosse Brinkhaus et al 2016b).…”
Section: Forage Legumes and Harvestmentioning
confidence: 99%
See 1 more Smart Citation
“…No mineral fertilizer was applied. To obtain three independent replicates (batches) per legume, fields were subdivided in three plots and sampling between two plots was performed at a distance of approximately 150 m (Grosse Brinkhaus et al 2016b).…”
Section: Forage Legumes and Harvestmentioning
confidence: 99%
“…The insoluble portion of CT is interesting from an animal nutrition perspective as it has been shown that protein-bound CT can dissociate in the small intestine of ruminants and makes protein available for digestion (Kariuki and Norton, 2008). In addition, the study of Grosse Brinkhaus et al (2016b) showed that an OvP silage, with 60% of protein-bound CT, supplied more duodenally utilisable crude protein relative to total crude protein than other legumes. The increase in protein-and fibre-bound CT fractions confirms results obtained on sainfoin by Scharenberget al (2007b) who compared hay and silage and by Terrill et al (2007) who showed that pellets of Sericea lespedeza contained mainly protein-bound CT.…”
Section: Effect Of Wilting Ensiling and Pelleting On Ct Content And mentioning
confidence: 99%
“…Sainfoin is 117 usually cut and used fresh or preserved as hay or pellets, while grazing is restricted to dry areas with 118 moderate irrigation (Wilman and Asiedu 1983). In addition, a large potential for silage production 119 has also been reported (Copani et al 2016;Grosse Brinkhaus et al 2016). Dry matter yields range 120 between 2 and 12 t ha -1 and are therefore considerably lower when compared to alfalfa or red clover 121 (Table 1; Frame et al 1998).…”
Section: Sainfoin -A Promising Forage Legume 114mentioning
confidence: 99%
“…Hydrolyzable tannins are not considered here, although evidence is emerging that some may exert similarly useful bioactive effects Engström et al, 2016;Bee et al, 2017). Hydrolyzable tannins are not considered here, although evidence is emerging that some may exert similarly useful bioactive effects Engström et al, 2016;Bee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although plants synthesize many different tannin types, this review will focus on CTs, as these are of particular interest in forage legumes and several other pasture plants. Hydrolyzable tannins are not considered here, although evidence is emerging that some may exert similarly useful bioactive effects Engström et al, 2016;Bee et al, 2017).…”
mentioning
confidence: 99%